Modulatory effect of Drosera peltata J.E.Sm on development of metabolic syndrome in tumor bearing mice - Raju A; Seeja S Raj; Christina AJM (Indonesian Journal of Pharmacy, 2016)
The purpose of the study conducted was to know the extent of protection over the cancer associated metabolic syndrome development after administration of ethanol and aqueous extracts of Drocera peltata against Dalton’s ascites lymphoma (DAL) and Ehrlich's Ascites Carcinoma (EAC) bearing mice. Animals were divided into thirteen groups with a normal control, EAC control, DAL control, two groups with standard drug 5-Flurouracil 20mg/kg+ DAL & EAC and eight groups with 250 and 500 mg/kg of ethanol and aqueous extracts of D.peltata + EAC & DAL, for respective cell lines. After 24 hours of both tumor cell inoculation, animals were treated with extracts,once in a day for 14 days continuously. The indicators for the development of metabolic syndrome such as changes in blood glucose, serum hormone and lipid profile were found with both cell line bearing mice. Both ethanol and aqueous extracts of D.peltata at doses of 250 and 500mg/kg significantly reduced the elevated blood glucose, hormonal and lipid profile changes. These results confirmed that ethanol and aqueous extracts  can stabilize the tumor induced hormonal, blood glucose and lipid profile changes in tumor bearing mice. This effect might be due to the presence of pharmacologically active phytoconstituents in extracts.